2021
DOI: 10.1007/jhep04(2021)157
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization in different phases of charged SYK model

Abstract: We study thermalization of charged SYK model in two different phases. We show that both the highly chaotic liquid phase and the dilute gas phase thermalize. Surprisingly the dilute gas state thermalizes instantaneously. We argue that this phenomenon arises because the system in this phase consists of only long-lived quasi-particles at very low density. The liquid state thermalizes exponentially fast. We also show that the additional introduction of random mass deformation (q = 2 SYK term) slows down thermaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The chaotic dynamics is increasingly suppressed when the q = 2 coupling strength is increased but the system is never completely integrable. This agrees with high precision calculation of the Lyapunov exponent of this system [22]. The Lyapunov exponent never goes to zero completely.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The chaotic dynamics is increasingly suppressed when the q = 2 coupling strength is increased but the system is never completely integrable. This agrees with high precision calculation of the Lyapunov exponent of this system [22]. The Lyapunov exponent never goes to zero completely.…”
Section: Introductionsupporting
confidence: 89%
“…One of the most important consequences of these results is that thermalization could be state-dependent. This is the subject of our ongoing work [22]. We also would like to point out that interesting gravity configurations with no black hole formation have been found [32,33].…”
Section: Introductionmentioning
confidence: 85%
“…A Planckian lifetime has also been obtained by nonequilibrium studies of SYK models, which display a recovery of thermal Green's functions in a time that is independent of U , and proportional to the inverse final temperature (Almheiri et al, 2019;Bhattacharya et al, 2019;Dhar et al, 2019;Eberlein et al, 2017a;Kourkoulou and Maldacena, 2017;Lensky and Qi, 2021;Rossini et al, 2020;Samui and Sorokhaibam, 2021;Zhang, 2019); for closely related and complementary insights, see also (Cheipesh et al, 2020;Haldar et al, 2020;Haque and McClarty, 2019;Kuhlenkamp and Knap, 2020;Larzul and Schiró, 2021;Sonner and Vielma, 2017).…”
Section: Non-zero Temperaturesmentioning
confidence: 87%
“…In the large N limit it was shown that the system thermalizes to an equilibrium state at infinite temperature, unless the initial state is a correlated thermal state of the mixed SYK 4 +SYK 2 which lead to a finite effective temperature. More recent works have focused on the dynamics of mixed SYK models with complex fermions [25] or deformation of the SYK model possesing a quantum phase transition [26]. In the high-energy literature the dynamics of pure states in the SYK model have attracted some interest [27] in particular the dynamics of entanglement entropy [28].…”
Section: Introductionmentioning
confidence: 99%